2008
DOI: 10.1038/emboj.2008.147
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MAP kinase 4 regulates gene expression through transcription factor release in the nucleus

Abstract: Plant and animal perception of microbes through pathogen surveillance proteins leads to MAP kinase signalling and the expression of defence genes. However, little is known about how plant MAP kinases regulate specific gene expression. We report that, in the absence of pathogens, Arabidopsis MAP kinase 4 (MPK4) exists in nuclear complexes with the WRKY33 transcription factor. This complex depends on the MPK4 substrate MKS1. Challenge with Pseudomonas syringae or flagellin leads to the activation of MPK4 and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
412
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(433 citation statements)
references
References 44 publications
(93 reference statements)
17
412
1
3
Order By: Relevance
“…The D motif within several WRKY TFs contains consensus phosphorylation sites for MAP kinases, and several WRKY TFs have been shown to be phosphorylated in vitro (Kim and Zhang, 2004;Menke et al, 2005;Eulgem and Somssich, 2007;Popescu et al, 2009). Recently, the association of MAP Kinase4 (MPK4) with AtWRKY33 and a coupling factor, MKS1, within the plant cell nucleus was demonstrated (Qiu et al, 2008b). Upon virulent P. syringae infection, MPK4 is phosphorylated, thereby releasing MKS1 and WRKY33 and thus allowing recruitment of WRKY33 to target promoters.…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D motif within several WRKY TFs contains consensus phosphorylation sites for MAP kinases, and several WRKY TFs have been shown to be phosphorylated in vitro (Kim and Zhang, 2004;Menke et al, 2005;Eulgem and Somssich, 2007;Popescu et al, 2009). Recently, the association of MAP Kinase4 (MPK4) with AtWRKY33 and a coupling factor, MKS1, within the plant cell nucleus was demonstrated (Qiu et al, 2008b). Upon virulent P. syringae infection, MPK4 is phosphorylated, thereby releasing MKS1 and WRKY33 and thus allowing recruitment of WRKY33 to target promoters.…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 99%
“…ChIP studies in parsley identified two PcWRKY1 target genes activated upon PAMP treatment (Turck et al, 2004). Similarly, PAD3, a gene encoding a key enzyme of camalexin biosynthesis, was detected as a direct target of AtWRKY33 following pathogen infection (Qiu et al, 2008b). Recently, using information derived from whole-genome microarrays followed by ChIP analyses, we identified two key regulators of plant defense as being direct targets of AtWRKY40 during powdery mildew infection (S.P.…”
Section: Pathogen-dependent In Vivo Wrky Tf Targets In the Postgenomimentioning
confidence: 99%
“…However, activated MPK4 phosphorylates VQ21, leading to the release of VQ21 and WRKY33 from MKP4. Consequently, WRKY33 binds to the promoter of PHYTOALEXIN DEFICIENT3 (PAD3), which encodes an enzyme required for the synthesis of antimicrobial camalexin (Andreasson et al, 2005;Qiu et al, 2008). This mechanism may ensure that VQ21 facilitates the recruitment of the kinase to WRKY factors to activate the MPK4-regulated signaling pathway (Fig.…”
Section: Mode Of Action Of Vq Proteinsmentioning
confidence: 99%
“…Interestingly, MKS1 also interacts with the transcription factors WRKY25 and WRKY33 (Andreasson et al, 2005). The interaction of MKS1 with WRKY33 depends on the phosphorylation status of MKS1 by MPK4 (Qiu et al, 2008a). In the absence of pathogens, inactivated MPK4 forms a ternary complex with MKS1 and WRKY33 in the nucleus, which prevents WRKY33 from functioning as a transcription factor (Qiu et al, 2008a).…”
mentioning
confidence: 99%
“…The interaction of MKS1 with WRKY33 depends on the phosphorylation status of MKS1 by MPK4 (Qiu et al, 2008a). In the absence of pathogens, inactivated MPK4 forms a ternary complex with MKS1 and WRKY33 in the nucleus, which prevents WRKY33 from functioning as a transcription factor (Qiu et al, 2008a). Upon activation of MPK4 by challenge with Pseudomonas syringae or flagellin, MKS1 is phosphorylated, and subsequently, phosphorylated MKS1 and WRKY33 proteins are released from MPK4.…”
mentioning
confidence: 99%